Asentamientos poblacionales en zonas vulnerables de la ciudad de Quevedo y sus efectos económicos y ambientales. Año 2012. Plan de reubicación. - Garcés Estrella, Carlos Alberto (2013)
The study is an approach to the sector of the river Island Quevedo and its surrounding areas whose settlements established there are affected in both dry and rainy season. It is on two distinct areas 1) A part located along a strip of marsh approximately 1.366 meters in length, variable width being its widest part of 47 meters from the Island in the River Quevedo, which covers an area of about 3.7 hectares, where they have located several groups of inhabitants and 2) On the other hand that corresponds to a sector more dry and consolidated but equally concerned with the floods in the rainy weather, which cover an extension of approximately 67 hectares. The main results of the investigation showed that the form of disposal of wastewater from the homes they are going to septic tanks, some of which are in flood prone areas. In other homes directly deposit them at the old chanver of the river and cause pollution that affects its inhabitants. This is due to the fact that there is no public sewer system. The Island in the River Quevedo and its surrounding areas generate economic costs and environmental the same that are reflected in the analysis of basic services and the costs you have to do the Government Decentralized Autonomous of Quevedo (GAD) and it affects the lack of public sewers in the environmental part. Despite the public’s perception about the affectation that has to do with septic tanks, people do nothing to solve the problem. The relocation of the inhabitants settled in the riverbed old in another area is the solution in the improvement of the quality of life, by this is proposing a plan that would allow us to give solution to the problem.